Kesiapan belajar daring dan kesejahteraan psikologis mahasiswa Indonesia di masa pandemi: Stres akademik sebagai moderator - Sari Zakiah Akmal; Dewi Kumalasari (Konsorsium Psikologi Ilmiah Nusantara, 2022)
The pandemic forces students to change their learning process from face to face into online learning. Not all students demonstrate readiness to overcome this pandemic and some of them experience academic pressure. This study aims to investigate whether stress caused by online learning is a moderator of the relationship between online learning readiness and college students’ well-being amid COVID-19 pandemic. Participants of this study were 293 undergraduate students (Mage = 20.42, SD = 1.87) hired using accidental sampling methods. The variables were measured through College Student Subjective Well-Being Questionnaire, Online Learning Readiness Scale, Stressor Scale for College Student (Study-Related Stressor subscale). Results showed that academic stress reduces the positive effect of online learning readiness toward college students’ well-being. The theoretical and practical implications are further discussed.